Israeli drama and the Bible: kings on the stage - Abramson, Glenda (AJS review, 2004)
Drama is the most neglected genre within Hebrew cultural development. In fact, until shortly before the foundation of the State of Israel, few plays in Hebrew had been staged. Although a large number of works in dramatic form had been written, particularly in the nineteenth century, few of them were viable theatrical dramas. They fell into the categories of rhetoric and allegory, devoid of believable dramatis personae. There were some milestones along the way, such as Somi's Zahut Bedihuta de-Kiddushin (An Eloquent Marriage Farce, c. 1600), Luzzatto's Leyesharim tehilla (Praise for the Righteous, 1743), and some modern plays, but these were not sufficiently feasible for the establishment of a dramatic tradition. An important factor qualifying the late development of Hebrew drama was the language, for within the communities' diglossia throughout the ages, Hebrew was reserved for more elevated discourse than playacting. Moreover, Hebrew, the language of the sacred texts, was inadequate for the expression of everyday life. Nowhere in the diaspora was there a Hebrew-speaking audience; there was no folk life in Hebrew as there was in Yiddish. Also, the potential playwrights were faced with the problem of the divine imperative in Jewish history, which precludes anything like the theodicy that gave rise to classical tragedy. Other religious restrictions against certain forms of representation, together with the small value Jewish religious authorities traditionally placed on theatre for its own sake, were also crucial factors mitigating against the drama's development.